Postradiation Histiocytic Sarcoma in the Setting of Muir-Torre Syndrome. (24th April 2018) - Baumgartner, Erin; Ullman, David; Jones, Jeffrey Adam; Fasciano, Danielle; Atherton, Daniel S.; Pavlidakey, Peter; Peker, Deniz
Abstract : Hereditary nonpolyposis colorectal carcinoma (HNPCC) is an autosomal dominant genetic disorder characterized by a predisposition towards colorectal carcinoma and other extracolonic neoplasms. Histiocytic sarcoma (HS) is a very rare hematologic neoplasm characterized by a malignant proliferation of cells with histiocytic differentiation. We present the case of a 62-year-old male with previous diagnosis of MTS who presented with metastatic colorectal adenocarcinoma, bilateral papillary renal cell carcinoma, and a new squamous cell carcinoma of the scalp, treated with resection and adjuvant radiation therapy. After reconstructive surgery for his scalp resection, the patient developed a persistent nonhealing skin defect. A punch biopsy of this nonhealing skin defect and subsequent immunohistochemistry revealed neoplastic histiocytic cells restricted to the epidermis and underlying dermis. The diagnosis of cutaneous histiocytic sarcoma was then rendered. Histiocytic sarcoma is an exceptionally rare malignancy. Consequently, there is no universally agreed upon management protocol for this malignancy. The patient was admitted to hospice and treated with palliative radiation. This case demonstrates the need for awareness of the risk of secondary malignancies in cancer patients in order to facilitate early surgical intervention and optimal treatment.